The Effect of the Pre-Heating Stage on the Microstructure and Texture of a Cold Rolled Fecmnalsi Steel Under Conventional and Ultrafast Heating - Castro-Cerda, F (Elsevier Inc., 2017)
This work focuses on the effect of a pre-heating stage on the microstructure evolution during continuous heating of 50% and 75% cold-rolled low carbon steel under conventional and ultrafast heating rates. Peak annealing experiments under two heating rates (10 °C/s and 400 °C/s) are applied to the samples after a pre-heating stage of 10 s. The selected pre-heating temperatures (300 °C and 400 °C) show an influence on the phase fraction of austenite formed after a short holding time in the intercritical (α + γ) phase field, and an effect on the intensity of recrystallized ferrite texture components. A refinement of ferritic average grain diameter is observed after increasing the heating rate from 10 °C/s to 400 °C/s. It is concluded that a pre-heating stage has a negligible impact on the microstructure and texture of cold-rolled low carbon steel. Therefore, a suitable technological window for the application of ultrafast heating rates in steel processing is enabled. © 2017 Elsevier Inc.